2010
DOI: 10.1016/j.molcel.2010.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Metabolic Gene Regulatory Network Downstream of mTOR Complex 1

Abstract: Aberrant activation of the mammalian target of rapamycin complex 1 (mTORC1) is a common molecular event in a variety of pathological settings, including genetic tumor syndromes, cancer, and obesity. However, the cell intrinsic consequences of mTORC1 activation remain poorly defined. Through a combination of unbiased genomic, metabolomic, and bioinformatic approaches, we demonstrate that mTORC1 activation is sufficient to stimulate specific metabolic pathways, including glycolysis, the oxidative arm of the pent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

69
1,646
2
21

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,678 publications
(1,792 citation statements)
references
References 44 publications
69
1,646
2
21
Order By: Relevance
“…Hyperactivity of mTORC1 is sufficient to increase HK-II expression 52 and a recent comprehensive and unbiased analysis also supports mTORC1-mediated HK-II upregulation and further demonstrated that mTORC1 signaling activates the genes encoding nearly every step of glycolysis. 53 Hypoxia-inducible factor 1 (HIF-1) is a transcription factor. The α-subunit of HIF-1 (HIF-1α) is stabilized under hypoxic conditions, leading to the activation of a transcriptional program to adapt to the lack of oxygen.…”
Section: Hexokinase II In Metabolismmentioning
confidence: 99%
“…Hyperactivity of mTORC1 is sufficient to increase HK-II expression 52 and a recent comprehensive and unbiased analysis also supports mTORC1-mediated HK-II upregulation and further demonstrated that mTORC1 signaling activates the genes encoding nearly every step of glycolysis. 53 Hypoxia-inducible factor 1 (HIF-1) is a transcription factor. The α-subunit of HIF-1 (HIF-1α) is stabilized under hypoxic conditions, leading to the activation of a transcriptional program to adapt to the lack of oxygen.…”
Section: Hexokinase II In Metabolismmentioning
confidence: 99%
“…In SCs, but not in OLs, the transcription factor RXRγ was shown to be transcriptionally regulated by mTORC1 and to control, in turn, the transcription of SREBP1c downstream of mTORC1 (Lebrun‐Julien et al, 2014; Norrmén et al, 2014). Differently from other cell types (Düvel et al, 2010; Owen et al, 2012), the mTORC1 target S6K is probably not majorly involved in regulating SREBPs. Thus, myelinating cells seem to possess specific mechanisms to regulate SREBPs and the expression of enzymes for lipid synthesis, with the additional twist that these mechanisms are probably different between SCs and OLs.…”
Section: Myelination and Mtormentioning
confidence: 83%
“…Subsequently, mature SREBPs induce the expression of several enzymes involved in fatty acid and cholesterol synthesis (Porstmann et al, 2008). Although the exact mechanisms are not yet defined, S6K1 has been implicated in this process (Düvel et al, 2010; Owen et al, 2012). In addition, mTORC1 was shown to modulate the actions of mature SREBPs by regulating the localization of lipin‐1.…”
Section: Mtor and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…mTORC1 and MYC have overlapping functions, including stimulating effects on cell growth and proliferation, ribosome biogenesis, and protein synthesis. In addition, mTORC1 induces oxidative phosphorylation by facilitating YY1/PGC1α complex formation (Cunningham et al , 2007) and supports aerobic glycolysis (Duvel et al , 2010). In the Eμ‐Myc mouse model, mTORC1 activation was shown to accelerate lymphomagenesis by inhibiting Myc‐induced apoptosis through translational upregulation of the anti‐apoptotic protein myeloid cell leukemia 1 (Mcl1; Mills et al , 2008), suggesting a collaboration of Myc and mTORC1 in tumor initiation.…”
Section: Discussionmentioning
confidence: 99%